Budaya Profil Pelajar Kreatif: Menumbuhkembangkan Literasi Visual Anak Panti Asuhan - Meggy Novitasari; Sutama Sutama; Ima Aryani; Qonitah Fauziyah; Isnaini Budi Utami (Warta LPM, 2024)
Community Service Partners (PkM), namely the Abdurrahman Bin Auf Orphanage (PA. Abd R.) Nogosari District, Boyolali. P.A. Abd R. currently has 49 foster children (M=23; P=26). The main problem in PA. Abd R., knowledge related to visual literacy and creativity is less than optimal with a percentage of 42%. So that foster children have visual literacy competencies, they need development and assistance so that they can continue their education to a higher, superior and competent level. The aim of the PkM program is to empower PA foster children. Abd R. through socialization, mentoring, and displays of visual literacy creativity to form habits. The expected impact of this program is that foster child partners will have an understanding of the material, expertise, creativity and skills in making learning media. Methods for implementing the PkM program, namely socialization, mentoring and showing creativity. The results of PkM activities are 1) Increased awareness and interest in learning for foster children in a visual literacy culture through socialization, mentoring and training. 2) Increasing the visual literacy skills of foster children that are culturally oriented towards creative student profiles. 3) Adequate learning resources/visual literacy reading books in the library (provided by the PkM team, adding 29 book titles). 4) Developing creativity from activities, a) working on Pre-test questions, b) making Popup books and booklets, c) making digital posters, d) making 3-dimensional wall magazines, e) making padlets, and f) working on Post-tests.